On Critical Thinking Skills: Investigating Students’ Analytical Exposition Essay - Agus Supriyadi (UMBanjarmasin, 2024)
This study aims at investigating students’ critical thinking in writing analytical exposition text. It employed qualitative descriptive approach. The subjets of study were second year students of SMA Negeri 2 Batu, taking Elective English Subject. One of the instructional objectives for this text is that students was able to write and present analytical text with objective of convincing the readers. Students’ essays of analytical exposition are then analyzed by using Illinois Crtical Thinking Skill. It consists of six features. They are Focus, Supporting Reason, Reasoning, Organizaing, Convention and Integration. Each feature is then scored by using score of 1-6. The finding show that the average score obtained is 2.88. It indicates that that Students Critical Thinking Skills are still on early level of development. Abstract Title written with Arial 11 Bold Center. Consists of a maximum of 200 words. It only consists of one paragraph and no special subtitles. The content of the abstract is the Introduction cultivated in one paragraph. The method is brief. The results are written in general and can contain numbers of research results. Conclusions are filled with brief conclusions from the conclusions that have been made on the content. References are not allowed to be included in the abstract or are not allowed to include citations.